The Influence of Service Quality, Product Quality, Price Perception and Location on Visitor Satisfaction - Fauzi, Ahmad; Suyana, Hilma; Oktavia, Dinda (SAN Scientific, 2023)
The goal of this study is to ascertain how consumer satisfaction at Lawson Salemba is impacted by product quality, price, and service quality. The consumers of Lawson Salemba make up the population under study. There were 130 responders in total, and a non-probability sampling strategy was employed. We used a survey instrument and survey methodology, and data was gathered. Multiple regression analysis is the data analysis technique employed. The study's findings demonstrate that location, product quality, price perception, and service quality all have a favorable and substantial impact on customer satisfaction. The managerial implications of this research are improving service quality by implementing high service standards and ensuring that each team member understands and implements these standards, assessing pricing strategies, and ensuring that the prices set are in line with customer perceptions of the value of the product or service, implementing a quality control system and monitor customer feedback regularly and analyze geographic and demographic data to assess whether the location can be optimized or whether it is necessary to open a branch in a more strategic location.